Determination of Optimal Coronary Flow for the Preservation of "Donation after Circulatory Death" in Murine Heart Model. Issue 2 (March 2018) - Quader, Mohammed; Toldo, Stefano; Torrado, Juan; Mishra, Suraj; Mauro, Adolfo G.; Mezzaroma, Eleonora; Heather, Reichstetter; Abbate, Antonio; Kasirajan, Vigneshwar; Mangino, Martin
Abstract : Donation after circulatory death donors (DCD) have the potential to increase the number of heart transplants. The DCD hearts undergo an extended period of warm ischemia, which mandates the use of machine perfusion preservation if they are to be successfully recovered for transplantation. Because the minimum coronary artery flow needed to meet the basal oxygen demand (DCRIT ) of a DCD heart during machine perfusion preservation is critical and yet unknown, we studied this in a DCD rat heart model. Adult male rats were anesthetized, intubated, heparinized, and paralyzed with vecuronium. The DCD hearts (n = 9) were recovered 30 minutes after circulatory death whereas non-DCD control hearts (n = 12) were recovered without circulatory death. Hearts were perfused through the aorta with an oxygenated Belzer Modified Machine Perfusion Solution (A3-Bridge to Life Ltd. Columbia, SC) at 15°C or 22°C starting at a flow index of 300 ml/100 g/min and decreasing by 40 ml/100 g/min every 10 minutes. Inflow (aortic) and outflow (inferior vena cava) perfusate samples were collected serially to assess the myocardial oxygen consumption index (MVO2 ) and O2 extraction ratio. The DCRIT is the minimum coronary flow below which the MVO2 becomes flow dependent. The MVO2, DCRIT, and oxygen extraction ratios were higher in DCD hearts compared with control hearts. The DCRIT for DCD hearts was achieved only at 15°C and was significantly higher (131.6 ± 7 ml/100 g/min) compared with control hearts (107.7 ± 8.4 ml/100 gm/min). The DCD hearts sustain warm ischemic damage and manifest higher metabolic needs during machine perfusion. Establishing adequate coronary perfusion is critical to preserving organ function for potential heart transplantation.